PEMBUATAN PROTOTYPE ALAT ELECTRO PLATING UNTUK - Tia Setiawan; Zenal Abidin; Cucu Hendra (Jurnal Ilmiah Teknologi Infomasi Terapan, 2021)
Corrosion is an electrochemical reaction process that is natural and takes place by itself, corrosion cannot be prevented or stopped but can only be controlled using the Electro Plating method. Electroplating is a process that produces a thin layer of metal on top of another metal surface by electrolysis or electroplating using direct current (DC) and chemical solutions (electrolytes). The process of giving this protective layer aims to protect the metal from corrosion, in this study, will make a prototype electro plating tool for small industry or Home Industry, the completeness of the components needed to make a prototype electro plating tool is an AC transformer matic 30-50 A 12V, ampere meter, volt meter, fuse and switch, then nickel solution serves to provide strength, metal resistance from rust and chrome solution serves to provide resistance to corrosion and gives a glossy white color so it looks better, to produce a strong coating. With the occurrence of the anode, cathode, and electrolyte solution which are used entirely as related to coating materials, especially metals are illustrated as, the cathode can be interpreted as the workpiece to be coated, connected to the negative pole of the electric current source and the electrolyte in the form of a solution whose molecules can be dissolved. in water and decomposes into positively or negatively charged particles and the deposition in the process is due to the presence of ions in the electrolyte and will settle on the cathode and the process of coating the metal occursPlease write your abstract in English version here.